2020
DOI: 10.1596/1813-9450-9221
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of COVID-19 and Connections with Air Pollution Exposure: Evidence from the Netherlands

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 27 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…The results show no significant differences between the two correlations used even if Pearson’s R are slightly higher for T d -PM 10 and PM 2.5 -PM 10 : 0.2485 and 0.8993, respectively. While, as confirmed by the literature (Andrée, 2020), a very strong positive correlation between PM 10 and PM 2.5 exists (R = 0.8993 and 0.8669 with Pearson and Spearman, respectively) it is however evident that the correlation between PM and the doubling time of the number of infected people (inversely proportional to propagation speed of the epidemic) is positive and substantially low. In fact, the indices of correlations given by Pearson and Spearman were 0.2485 and 0.1954, respectively.…”
Section: Resultssupporting
confidence: 68%
“…The results show no significant differences between the two correlations used even if Pearson’s R are slightly higher for T d -PM 10 and PM 2.5 -PM 10 : 0.2485 and 0.8993, respectively. While, as confirmed by the literature (Andrée, 2020), a very strong positive correlation between PM 10 and PM 2.5 exists (R = 0.8993 and 0.8669 with Pearson and Spearman, respectively) it is however evident that the correlation between PM and the doubling time of the number of infected people (inversely proportional to propagation speed of the epidemic) is positive and substantially low. In fact, the indices of correlations given by Pearson and Spearman were 0.2485 and 0.1954, respectively.…”
Section: Resultssupporting
confidence: 68%
“…Ecological studies. Most studies that investigated chronic exposure to air pollution and COVID-19 used an ecological design (Andrée 2020;Cui et al 2003;Ogen 2020;Travaglio et al 2020a;Wu et al 2020). Ecological studies have a long history in epidemiology, and started with John Snow's investigation of cholera in London in the mid-1800s (Snow 1856).…”
Section: Study Designsmentioning
confidence: 99%
“…A study on collected data from the US Environmental Protection Agency (EJSCREEN) showed a positive correlation between COVID‐19 infections and deaths with higher levels of diesel particulate matter (DPM) (Hendryx & Luo, 2020). In the Netherlands, a study using data from 355 municipalities indicated PM 2.5 as an important indicator of COVID‐19 incidence and hospital stay (Andree, 2020). An increased pollutant concentration by 20% was related to almost 100% of COVID‐19 incidence (Andree, 2020).…”
Section: Resultsmentioning
confidence: 99%